Prevalence of metabolic syndrome in patients attending general practice outpatient department at a community hospital - Pradhan, Binita; Pakhrin, Reema; Pandey, Sujan; Bista, Raunak; Pradhan, Sailesh Bahadur (Journal of Kathmandu Medical College, 2022)
Background: Metabolic syndrome, a cluster of metabolic abnormalities which bears increased risk for cardiovascular diseases and diabetes mellitus, requires early screening, diagnosis, and timely intervention. Prevalence varies with age, gender, degree of obesity, and increased propensity for type 2 diabetes mellitus. Objectives: To find out the prevalence of metabolic syndrome among individuals with hypertension and/or diabetes seeking medical evaluation in general practice outpatient department of Kathmandu Medical College Community Hospital. Methods: This cross-sectional analytical study was conducted among 100 participants collected by convenience sampling at general practice outpatient department of Kathmandu Medical College Community Hospital, Duwakot, Bhaktapur, Nepal. Physical examination was done and investigations were sent. Metabolic Syndrome was diagnosed using US National Cholesterol Education Program Adult Treatment Panel. Data collection was done from 2019 July to 2019 December. Study population was patients with either hypertension and/or diabetes seeking medical evaluation, age of 18 years or above, both genders, no known comorbidity other than those under medication for hypertension and diabetes. Data analysis was done with SPSS v.16 and two-sample t-test or Chi-square test applied as appropriate. A p-value <0.05 taken as statistically significant. Results: Out of 100 individuals, 73 were found having metabolic syndrome. It was more common among male (38, 52.1%), obese people of age 40-59 years (42, 57%), and among patients with high body mass index (26.93±2.74). Conclusion: The prevalence of metabolic syndrome was found significantly high among patients with hypertension or diabetes. Therefore, it is important to diagnose this condition on time to prevent subsequent complications.